Correlation between cord blood apelin and IGF-1 levels in retinopathy of prematurity. (December 2012) - Cekmez, Ferhat; Pirgon, Ozgur; Aydemir, Gokhan; Dundar, Bumin; Çekmez, Yasemin; Karaoglu, Abdulbaki; Fidanc, Kürsat; Tunc, Turan; Aydinoz, Secil; Karademir, Ferhan; Süleymanoglu, Selami
Aim: We hypothesized that circulating apelin concentrations in preterm babies might be linked with retinopathy of prematurity (ROP), similar to IGF-1 levels.Patients & methods: A total of 97 infants born with a gestational age before 32 weeks in 2007–2009 were screened for ROP at the Gata Haydarpasa Hospital (Turkey). Fourteen of them with classified ROP stage 3–5 comprised our study group.Results: The non-ROP group had higher apelin and IGF-1 levels than ROP neonates at birth. After 4–6 weeks, postnatal ROP subjects had lower apelin and IGF-1 levels than non-ROP controls. At the end of the study, the change in apelin levels was positively correlated with the change in IGF-1 levels (r = 0.852; p = 0.01).Conclusion: We suggested that the pathogenesis of ROP, which is regarded as a neovascular retinal disorder, includes variations in the levels of apelin and IGF-1.